A STUDY OF RELATION BETWEEN BODY MASS INDEX AND DYSMENORRHEA AND ITS IMPACT ON DAILY ACTIVITIES OF MEDICAL STUDENTS - Mohapatra, Dipti; Mishra, Tapaswini; Behera, Manasi; Panda, Priyambada (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Dysmenorrhea is a condition, in which there is a severe, painful, cramping sensation in the lower abdomen which occurs just before or during the menses. It has a major impact on the quality of life and social and occupational roles of females in the society. It also results in insignificant work, school, and college absences in girls. As previous studies have failed to show a definite relation between dysmenorrhea and body mass index (BMI), the aim of our study was to find out an association between BMI and dysmenorrhea among medical students. Methods: The study was conducted on 200 medical students. Each one was supplied with a questionnaire with detailed menstrual history, family history of dysmenorrhea, and detailed H/O of physical exercise and dietary habits. BMI was calculated by the formula weight in kg/height2 in meter, and based on the BMI criteria by the World Health Organization, the students were classified into four groups: Underweight, normal, overweight, and obese groups. The data obtained were statistically analyzed by Pearson Chi-square test, and p<0.5 was considered significant. Result: From our study, we found out that there is a positive correlation between dysmenorrhea and low BMI. Conclusion: As there is a positive correlation between BMI and dysmenorrhea, our aim was to educate people about dysmenorrhea and create awareness on diet and dysmenorrhea to assist in improving the quality of life in females. Keywords: Dysmenorrhea, Body mass index, Quality of life.